Effect of acid treatment for reducing pores clogging in polyvinyl alcohol grinding stone
Grinding stone after aluminum disk grinding was clogged by debris loading after used for a certain period of time. The clogging pores modified the surface structure of grinding stone thus resulting in scratching of aluminum disk during grinding process. The aim of this thesis is to determine the properties of raw (control) and clogged (sample) grinding stone thus reduced the clogging problem in grinding stone using acid treatment. The grinding stone were characterized to understand the factor of pore clogging. Morphology analysis by scanning electron microscope (SEM) and elemental analysis using X-ray fluorescence (XRF) spectrometer found that, the clogging area were consist of debris from aluminum disk grinding. Pore size and distribution in unused grinding stone from micrograph structure were varied and inhomogeneous. Since size of debris cannot be controlled, there were some of debris size that larger than the pore size. Even though pore were connected each other as a tunnel for debris removal, the bigger debris size cannot flow through small hollow of pore which cause the loading of debris resulted in pore clogging. The pore size was not uniform, density and hardness (Shore A Durometer) of control grinding stone also were varied. The grinding stone were treated with three different types of acid (citric, phosphoric, and oxalic acid) at concentration of 0.5, 1.0, and 1.5 M with treatment time of 1, 30, and 60 minutes. Porosity results and micrograph structure of the grinding stone indicated that the acids can caused clogging in control grinding stone but had the ability to produce pores for sample grinding stone. At concentration of 1.0 M, oxalic acid shows the highest clogging removal compared to citric and phosphoric acid. However, elemental analysis by energy dispersive x-ray (EDX) spectroscopy shows that oxalic acid tend to remove silicon carbide (SiC) abrasive of grinding stone and phosphoric acid has the tendency to deposit in grinding stone. As conclusion, 1.0 M citric acid and stirring time of 1 minute was the optimum parameter for dissolving the pore clogging in sample grinding stone. Besides not affecting aluminum substrate, citric acid also the best chelating agent to dissolute aluminum debris in grinding stone while does not chelating with silicon carbide.